1981
DOI: 10.1007/bf02357035
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glucagon on the kinetics of hepatic mitochondrial calcium uptake

Abstract: Previous work by this and other laboratories has shown that glucagon administration stimulates calcium uptake by subsequently isolated hepatic mitochondria. This stimulation of hepatic mitochondrial Ca2+ uptake by in vivo administration of glucagon was further characterized in the present report. Maximal stimulation of mitochondrial Ca2+ accumulation was achieved between 6-10 min after the intravenous injection of glucagon into intact rats. Under control conditions, Ca2+ uptake was inhibited by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The correlation of Ca2+_flux changes with an increase in the calcium content of fractions enriched in mitochondria obtained by Percoll-density-gradient subfractionation of the liver after hormonal challenge strongly indicates that the Ca2+ taken up by the liver is accumulated by the mitochondria, a conclusion consistent with that of Morgan et al (1983a). The data also are consistent with previous observations from our and other laboratories that the administration of glucagon in vivo to rats, or to the perfused rat liver, greatly enhances the ability of the subsequently isolated mitochondria to retain Ca2+ (Hughes & Barritt, 1978;Prpic et al, 1978;Andia-Waltenbaugh et al, 1978, 1981Prpic & Bygrave, 1980;Taylor et al, 1980). Mauger et al (1985), who studied the stimulation of 45Ca2+ uptake induced by the combined addition of glucagon and Ca2+-mobilizing hormones using isolated hepatocytes, concluded that plasma-membrane Ca2+ channels are the principal sites affected.…”
Section: Discussionsupporting
confidence: 92%
“…The correlation of Ca2+_flux changes with an increase in the calcium content of fractions enriched in mitochondria obtained by Percoll-density-gradient subfractionation of the liver after hormonal challenge strongly indicates that the Ca2+ taken up by the liver is accumulated by the mitochondria, a conclusion consistent with that of Morgan et al (1983a). The data also are consistent with previous observations from our and other laboratories that the administration of glucagon in vivo to rats, or to the perfused rat liver, greatly enhances the ability of the subsequently isolated mitochondria to retain Ca2+ (Hughes & Barritt, 1978;Prpic et al, 1978;Andia-Waltenbaugh et al, 1978, 1981Prpic & Bygrave, 1980;Taylor et al, 1980). Mauger et al (1985), who studied the stimulation of 45Ca2+ uptake induced by the combined addition of glucagon and Ca2+-mobilizing hormones using isolated hepatocytes, concluded that plasma-membrane Ca2+ channels are the principal sites affected.…”
Section: Discussionsupporting
confidence: 92%
“…A large body of work showed, for instance, that administration of glucagon to intact rats will enhance the ability of the subsequently isolated microsomes to accumulate Ca21 in vitro (e.g. Bygrave and Tranter, 1978;Reinhart and Bygrave, 1981;Andia-Waltenbaugh et al, 1981). With mitochondria too, it was established that prior glucagon administration to the intact rat led to an increased ability of the subsequently isolated organelle to retain Ca2+ (e.g.…”
Section: Other Ca2+ Flux-related Signals Generated By Glucagonmentioning
confidence: 99%
“…siological role of this transport system has yet to be assessed. One established point relevant to this is that insulin is able to offset the stimulatory effects of glucagon (Waltenbaugh & Friedmann, 1978;Taylor et al, 1979;Waltenbaugh et al, 1980). Previously we have argued that considerable information can be gained about the physiological role of metabolite transport by organelles by studying changes in their activity during development, or as a result of some specific physiological perturbation (Bygrave, 1977).…”
mentioning
confidence: 99%
“…The very high rates of glycogenolysis that occur immediately after birth are believed to be induced by the high concentration of plasma glucagon (Girard et al, 1973(Girard et al, , 1974Blazquez et al, 1974;Bashan et al, 1979); injection of the hormone into foetuses is known to deplete stores of liver glycogen rapidly (Greengard & Dewey, 1970;Leskes et al, 1971). Since the regulation by glucagon of glycogenolysis in adult rat liver (Hales et al, 1977;Siess et al, 1977) is dependent on the redistribution of intracellular Ca2+ (see, e.g., Rylatt et al, 1979), it is of some interest from the metabolic viewpoint that a target of glucagon action in the liver is the Ruthenium Red-insensitive Ca2+-transport system (Bygrave & Tranter, 1978;Waltenbaugh & Friedmann, 1978;Taylor et al, 1979Taylor et al, , 1980b; the present work). One can envisage that the glucagon-induced rapid mobilization of Ca2+ from stores such as the mitochondria and the endoplasmic reticulum would stimulate the activity of phosphorylase kinase, the Ca2+-dependent enzyme that catalyses the conversion of phosphorylase b into phosphorylase a, and hence glycogen breakdown (see, e.g., Blackmore et al, 1978Blackmore et al, , 1979.…”
mentioning
confidence: 99%